Infectivity of Deinbollia mosaic virus, a novel weed-infecting begomovirus in East Africa - Kyallo, Martina M.; Ateka, Elijah Miinda; Sseruwagi, Peter; Ascencio-Ibáñez, José Trinidad; Ssemakula, Mildred-Ochwo; Skilton, Robert A.; Ndunguru, Joseph (Springer, 2017)
Weed-infecting begomoviruses play an important role in the epidemiology of crop diseases because they can potentially infect crops and contribute to the genetic diversity of crop-infecting begomoviruses. Despite the important epidemiological role that weed-infecting begomoviruses play, they remain insufficiently studied in Africa. Recently, we identified Deinbollia mosaic virus (DMV), a distinct begomovirus found naturally infecting the weed host Deinbollia borbonica (Sapindaceae) in Kenya and Tanzania. In this study, we investigated the capacity of DMV to infect a restricted host range of Solanaceae and Euphorbiaceae species. Biolistic inoculation of Nicotiana benthamiana with concatemeric DNAs resulted in systemic infection associated with yellow mosaic symptoms, while DNA partial dimers caused asymptomatic systemic infection. DMV was not infectious to cassava (Manihot esculenta Crantz), suggesting host resistance to the virus. Here, we demonstrate the first experimental infectivity analysis of DMV in N. benthamiana and cassava.